Kedudukan Badan Pengawas Pemilu Berdasarkan Undang-Undang Dasar 1945 - Salurante, Belona Danduru; Primayanti, Andi Dewi; Bruaharja, Isman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
In the history of the implementation of elections in Indonesia, the term election supervision actually only emerged in the 1980. In the implementation of the elections which were first held in Indonesia in 1955, the term election supervision was not yet known. In that era,trust was built among all participants and citizens regarding the implementation of elections which were intended to form a parliamentary institution which is currently it is called as constituent.Although the ideological conflict at that time was quite strong, it can be said that thre was very minimal fraud in the implementation of the stages,even if there was friction outside the area of the election,the friction that emerged was a the logical consequence of the ideological struggle at that time until now the belief that Bawaslu must be able to work synergistically with all elements of the nation Kata kunci: Election supervisory body and democratic system